Mass and containers labeled with the mass

The use of a low-viscosity hot melt adhesive in a mixed resin film bag with ethylene-vinyl acetate copolymer and polypropylene wax addresses cold flow issues, ensuring effective packaging and reduced environmental burden by preventing lump adhesion.

JP7620746B1Active Publication Date: 2025-01-23TOYO INK MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024019157
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-02-13
Publication Date
2025-01-23
Estimated Expiration
2044-02-13

AI Technical Summary

Technical Problem

Existing hot melt adhesives, particularly low-viscosity ones, suffer from cold flow during storage, leading to bag tearing and lump adhesion, which complicates packaging and environmental disposal of release materials.

Method used

A low-viscosity hot melt adhesive encapsulated in a melt bag made of a mixed resin film comprising low-density polyethylene and ethylene-vinyl acetate copolymer, with specific ratios and properties to enhance bag breakability and solubility, along with additives like polypropylene wax to improve stringiness.

Benefits of technology

The solution provides improved bag breakability, solubility, and stringiness, preventing lump adhesion and enhancing packaging efficiency while reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620746000001
    Figure 0007620746000001
  • Figure 0007620746000002
    Figure 0007620746000002
  • Figure 0007620746000003
    Figure 0007620746000003
Patent Text Reader

Abstract

To provide a lump having superior bag-breaking properties, solubility (compatibility) with contents, and stringiness during coating, compared to conventional lump even when a low-viscosity hot-melt adhesive is contained in the melt bag, and to provide a container with a label attached thereto using the lump. [Solution] A mass containing a hot melt adhesive in a melting bag, the melting bag having a density of 923 to 930 kg / m 3 The hot melt adhesive comprises a mixed resin film containing a low density polyethylene resin (A) and an ethylene-vinyl acetate copolymer resin (B), and the hot melt adhesive contains a wax (C) and has a viscosity of 500 to 2500 mPa s at 140°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mass containing a hot melt adhesive in a melting bag, and to a container to which a label is attached using the mass. [Background technology]

[0002] Hot melt adhesives melt and bond objects together, then they are left to cool and their adhesive properties appear immediately, so their advantage of not needing a curing period has been rediscovered, and their use is expanding in packaging and industrial applications. In response to recent social changes that emphasize reducing the burden on the environment, the advantage of not needing solvents or drying processes during use has also been rediscovered, and their use is continuing to expand.

[0003] As the range of applications for hot melt adhesives expands, there is a demand for improved workability. For example, in the summer, hot melt lumps stick together (blocking), and when removing them from the packed cardboard boxes, etc., they become huge lumps, which significantly reduces workability. Therefore, hot melt adhesives that are adhesive at room temperature in particular are packed, transported, and stored in a state wrapped in release paper or release film, which is peeled off and discarded when the hot melt adhesive is used, but the disposal of these release materials has also become a problem as an environmental burden.

[0004] Therefore, a specification using a so-called melting bag (lump) has been developed in which the hot melt adhesive is packaged in a hard material and melted while still packaged when used (Patent Document 1). Since the hot melt adhesive is melted while still packaged in the melting bag, the lump requires basic performance such as the solubility (compatibility) of the melting bag and the hot melt, and the bag breaking resistance when stored at high temperatures. The practical application of the lump has avoided the environmental burden caused by the disposal of release material, and has also eliminated the burden of peeling off the release material every time the lump hot melt adhesive is melted, significantly improving workability. Furthermore, in recent years, measures have been taken to prevent blocking, such as increasing the strength of the melt bag (Patent Document 2) or giving it an embossed shape (Patent Document 3).

[0005] Generally, polyethylene terephthalate bottles (hereinafter referred to as PET bottles) used for beverages and the like have labels attached thereto, and the labels are often wrapped around the bottle. Hot melt adhesives are generally used as adhesives for attaching the wraparound labels. For hot melt adhesives used for PET bottle labels, a low-viscosity hot melt with a viscosity of 2,500 mPa·s or less at 140°C is preferable in order to prevent the hot melt from scattering and contaminating the labeler in the form of threads (stringiness) when applying the label (Patent Document 4). With the increase in the use of PET bottles for beverages, there is an increasing demand for a mass of such low-viscosity hot melt packed in a melting bag, but there has been a problem in terms of the stringiness of the molten mass.

[0006] However, after investigations by the present inventors, it was found that in the inventions described in Patent Documents 1 to 3, when a low-viscosity hot melt is contained in a melt bag, the hot melt dissolves from the melt bag due to cold flow (the phenomenon in which the hot melt gradually deforms and spreads) during storage, and the melt bag breaks during packaging, exposing the hot melt adhesive to the surface, resulting in blocking between lumps. In other words, a mass containing a low-viscosity hot melt in a melt bag that satisfies the solubility of the melt bag and hot melt, the bag-breaking properties to prevent blocking, and the stringiness during coating had not yet been developed. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-002581 A [Patent Document 2] International Publication No. 2014 / 194087 [Patent Document 3] JP 2019-065164 A [Patent Document 4] Patent No. 4278704 Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, an object of the present invention is to provide a lump having better bag-breaking properties than conventional lump, excellent solubility (compatibility) with the contents, and excellent stringiness during application, even when a low-viscosity hot-melt adhesive with a viscosity of 500 to 2,500 mPa s at 140°C is contained in a melt bag, and to provide a container to which a label is attached using the lump. [Means for solving the problem]

[0009] The present disclosure provides the following masses and containers labeled with the masses: [1]: A mass containing a hot melt adhesive in a melting bag, The density of the melting bag is 923-930kg / m 3 A mixed resin film comprising a low-density polyethylene resin (A) and an ethylene-vinyl acetate copolymer resin (B), The hot melt pressure sensitive adhesive comprises a wax (C) and has a viscosity of 500 to 2500 mPa·s at 140°C.

[0010] [2]: The above lump, in which the content of the ethylene-vinyl acetate copolymer resin (B) in 100% by mass of the mixed resin film is 10 to 50% by mass.

[0011] [3]: The above lump, wherein the ethylene-vinyl acetate copolymer resin (B) has a vinyl acetate content of 5 to 30 mass %.

[0012] [4]: Low-density polyethylene resin (A) at 190°C, 2.16kgf / cm 2 The above aggregates are characterized in that the melt mass flow rate in this case is 1 to 25 g / 10 min.

[0013] [5]: The above lump, characterized in that the melting point of the wax (C) is 70 to 150°C.

[0014] [6]: The above lump, characterized in that the wax (C) contains at least one of a polyethylene-based wax (C-1) having a melting point of 90 to 150°C and a polypropylene-based wax (C-2) having a melting point of 90 to 150°C.

[0015] [7]: The above lump, characterized in that the thickness of the melt bag is 10 to 500 μm.

[0016] [8]: The above lump, characterized in that it contains a polypropylene-based wax (C-2) having a melting point of 90 to 150°C, and the wax (C-2) contains a polypropylene wax graft-polymerized with maleic anhydride.

[0017] [9]: The above lump, wherein the hot melt adhesive is an alkali dispersible hot melt adhesive.

[0018]

[10] : A container to which a label is attached using the above mass.

[0019]

[11] : The container as described above, characterized in that the material of the container is polyethylene terephthalate or glass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present disclosure will be described in detail below. It should be noted that other embodiments are of course included in the scope of the present disclosure as long as they conform to the spirit of the present disclosure.

[0021] In this specification, a numerical range specified by using "~" includes the numerical values ​​before and after "~" as the lower and upper limit ranges. In addition, unless otherwise noted, each of the various components appearing in this specification may be used independently, either alone or in combination of two or more types. In addition, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0022] In this specification, the "viscosity" was measured according to JIS K6862 (Melt viscosity test method for hot melt adhesives). In this specification, the "melt mass flow rate (hereinafter abbreviated as MFR)" was measured according to JIS K7210 (flow test method for thermoplastics). In this specification, the "melting point of the wax" is a value measured by a differential scanning calorimeter (Shimadzu automatic differential calorimeter DSC-60A Plus). In this specification, the "film thickness" was measured using a PEACOCK DIGITAL THICKNESS GAUGE G2-205 manufactured by Ozaki Seisakusho.

[0023] In this specification, the term "hot melt" refers to a material that is in a solid or viscous state at room temperature and melts and softens to become fluid or liquid when heated.

[0024] <Melting bag> The melting bag is used to package hot melt adhesives. However, this is not the case if the melting bag can contribute technically to products other than hot melt adhesives. The melting bag used in the present invention has a density of 923 to 930 kg / m 3 The melt bag is made of a mixed resin film containing low-density polyethylene resin (A) and ethylene-vinyl acetate copolymer resin (B). The melt bag can be made by heating and melting the mixed resin film and forming (manufacturing) it into a film by a known method. It is desirable for the film thickness of the melt bag to be as uniform as possible.

[0025] From the viewpoints of meltability and bag-breaking property, the mixed resin film contains preferably 50 to 90 mass% of low-density polyethylene resin (A) and more preferably 70 to 90 mass% based on 100% mass of the mixed resin film. From the viewpoints of bag-breaking property and solubility, the mixed resin film contains preferably 10 to 50 mass% of ethylene-vinyl acetate copolymer resin (B) and more preferably 10 to 30 mass% based on 100% mass of the mixed resin film.

[0026] The thickness of the melting bag is preferably 10 to 500 μm, more preferably 20 to 200 μm, and further preferably 30 to 100 μm. When the thickness is within the above range, it is easy to achieve both solubility and bag breaking properties.

[0027] [Low density polyethylene resin (A)] The density of low-density polyethylene (A) is 923 to 930 kg / m 3 The density is 923-930kg / m 3 From the viewpoint of melting property and bag-breaking property, the MFR of the low-density polyethylene resin (A) is preferably from 1 to 25 g / 10 minutes, and more preferably from 7 to 25 g / 10 minutes.

[0028] [Ethylene-vinyl acetate copolymer resin (B)] The ethylene-vinyl acetate copolymer resin (B) is not particularly limited as long as it is a copolymer of ethylene and vinyl acetate. The vinyl acetate content of the ethylene-vinyl acetate copolymer resin (B) is preferably 5 to 30% by mass, more preferably 10 to 25% by mass, from the viewpoint of bag breaking property and solubility. The vinyl acetate content is the content (% by mass) of vinyl acetate contained in the ethylene-vinyl acetate copolymer resin.

[0029] (Method of manufacturing mixed resin film) The method for producing the film used in the melt bag is not particularly limited as long as it can produce the hot melt pressure sensitive adhesive mass of the present invention, and examples of the method include known melt casting methods, T-die methods, inflation methods, etc. The thermoplastic film of the embodiment of the present invention may be a single layer film or a multilayer film consisting of two or more layers. The surface of the thermoplastic film may be roughened to form irregularities, but is not particularly limited as long as the object of the present invention is to obtain a mass containing the hot melt pressure sensitive adhesive.

[0030] <Hot melt adhesive> The hot melt pressure sensitive adhesive contains a wax (C) from the viewpoint of bag breaking properties and stringiness, and has a viscosity at 140° C. of 500 to 2000 mPa·s, more preferably 700 to 1300 mPa·s.

[0031] Wax Waxes (C) are broadly classified into natural waxes (animal waxes (beeswax, etc.), vegetable waxes (japanese wax, rice bran wax, etc.), mineral waxes (ozokerite, etc.), petroleum waxes (paraffin wax, microcrystalline wax, etc.)) and synthetic waxes (Fischer-Tropsch wax, polyethylene wax, polypropylene, and waxes modified with acids, etc.). Waxes (C) are used alone or in combination of two or more types.

[0032] The wax (C) preferably has a melting point of 70 to 150° C. in order to improve the breakability of the mass containing the hot melt adhesive in the melt bag.

[0033] The wax (C) preferably contains a polyethylene wax (C-1) having a melting point of 90 to 150° C. and / or a polypropylene wax (C-2) having a melting point of 90 to 150° C. By containing (C-1) and / or (C-2), the bag-breaking property of the lump can be improved. It is more preferable to contain a polypropylene wax (C-2) having a melting point of 90 to 150° C.

[0034] The polyethylene wax (C-1) is produced from ethylene and includes modified products such as those modified with maleic acid. For example, Polywax (manufactured by NuCera) and waxes modified with maleic acid are also included. For example, Sanwax (manufactured by Sanyo Chemical Industries, Ltd.) and Hiwax (manufactured by Mitsui Chemicals, Inc.) are included. Polypropylene wax (C-2) is mainly produced from propylene, and includes modified products such as those modified with maleic acid. Examples include block polypropylenes copolymerized with other monomers in blocks, such as Viscol (manufactured by Sanyo Chemical Industries, Ltd.), Hiwax NP series (manufactured by Mitsui Chemicals, Inc.), and Ricosene PP series (manufactured by Client Chemicals, Inc.). The polypropylene wax (C-2) is preferably a polypropylene wax graft-polymerized with maleic anhydride from the viewpoint of alkali dispersibility of the lump.

[0035] In addition to the wax (C), the hot melt adhesive may contain other ingredients such as a thermoplastic elastomer, a tackifier, an oil, a colorant, an antiblocking agent, an inorganic filler, an antioxidant, a bulking agent, a flame retardant, a plasticizer, an antistatic agent, a light stabilizer, an ultraviolet absorber, a heavy metal deactivator, and a fluorescent whitening agent.

[0036] (Thermoplastic elastomer) Thermoplastic elastomers are elastic materials that have the same properties as vulcanized rubber at room temperature, and at high temperatures they are polymeric materials that can be used with existing molding machines just like ordinary thermoplastic resins. Thermoplastic elastomers have both elastic rubber components in the molecules (soft segments: soft phase) and molecular restraint components (hard segments: hard phase) to prevent plastic deformation, so they have properties between rubber and plastic. Thermoplastic elastomers generally have a polystyrene block and a rubber middle block, with the polystyrene portion forming a physical crosslink (domain) and becoming the crosslinking point, and the middle rubber block giving the product rubber elasticity. The middle soft segment includes polybutadiene (B), polyisoprene (I) and polyolefin elastomers (ethylene-propylene (EP), ethylene-butylene (EB), butylene-butadiene (BB)), and depending on the arrangement with the hard segment polystyrene (S), they are divided into linear type and branched type (radial type).

[0037] (tackifier) Examples of the tackifier include phenolic resin, modified phenolic resin, terpene phenolic resin, xylene phenolic resin, cyclopentadiene-phenolic resin, xylene resin, aliphatic, alicyclic, aromatic petroleum resin, hydrogenated aliphatic, alicyclic, aromatic petroleum resin, phenol-modified petroleum resin, rosin ester resin, hydrogenated rosin, acid-modified rosin, hydrogenated rosin ester resin, low molecular weight polystyrene resin, terpene resin, hydrogenated terpene resin, etc. In particular, a tackifier having an acid value of 100 to 300 mgKOH / g is suitable for an alkali dispersion type hot melt adhesive. Examples include hydrogenated rosin and acid-modified rosin.

[0038] (oil) The oil is generally used as a plasticizer for rubber, thermoplastic elastomers, etc., i.e., process oil produced in petroleum refineries, etc., and is roughly classified into paraffinic process oil, naphthenic process oil, and aromatic process oil. Process oil is a mixture of aromatic rings, naphthenic rings, and paraffin chains, and naphthenic process oil in this application refers to process oil in which naphthenic ring carbons account for 35-46% by mass of the total carbon of the process oil. In addition, process oils in which aromatic carbons account for 30% by mass or more of the total carbon are classified as aromatic process oils, and process oils in which paraffin chain carbons account for 50% by mass or more of the total carbon are classified as paraffinic process oils.

[0039] (Coloring agent) The colorant may be a commonly used colorant such as red, blue, green, yellow, etc. The colorant may be any of pigments, dyes, and colorants, and examples of the colorant include monoazo, dizazo, azo lake, benzimidazolone, perylene, diketopyrrolopyrrole, condensed azo, anthraquinone, quinacridone, phthalocyanine, and anthraquinone, and examples of the pigment include pigment, perylene, monoazo, condensed azo, isoindolinone, titanium oxide, and carbon.

[0040] (Anti-blocking agent) Examples of the anti-blocking agent include silicones, unsaturated fatty acid amides such as stearic acid amide, oleic acid amide, erucic acid amide, oleic acid amide and behenic acid amide.

[0041] (Inorganic filler) Examples of inorganic fillers include particles and fibers of metals, metal oxides, and metal hydroxides. Specific examples include glass fibers, carbon fibers, calcium silicate, calcium titanate, aluminum borate fibers, flake glass, talc, kaolin, mica, hydrotalcite, calcium carbonate, zinc carbonate, zinc oxide, calcium hydrogen phosphate, wollastonite, silica, zeolite, alumina, boehmite, aluminum hydroxide, titanium oxide, silicon oxide, magnesium oxide, calcium silicate, alumina sodium silicate, magnesium silicate, carbon nanotube, graphite, copper, silver, aluminum, nickel, iron, calcium fluoride, mica, montmorillonite, and apatite.

[0042] (Antioxidants) Examples of the antioxidant include pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-t-butyl-4-hydroxy-m-tolyl]propionate, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, etc. These antioxidants may be used alone or in combination of two or more.

[0043] (Filler) Examples of the filler include wet silica, aluminum hydroxide, aluminum oxide, magnesium oxide, montmorillonite, mica, smectite, organically modified montmorillonite, organically modified mica, and organically modified smectite.

[0044] (Flame retardant) Examples of the flame retardant include phosphorus-containing compound-based flame retardants, halogen-containing compound-based flame retardants, sulfonic acid metal salt-based flame retardants, and silicon-containing compound-based flame retardants.

[0045] (Plasticizer) Examples of the plasticizer include phthalate ester plasticizers, polyester plasticizers, aliphatic dibasic acid ester plasticizers, aliphatic monobasic acid ester plasticizers, phosphate ester plasticizers, citrate ester plasticizers, epoxy plasticizers, trimellitate ester plasticizers, tetrahydrophthalate ester plasticizers, glycol plasticizers, and bisphenol A alkylene oxide derivatives.

[0046] (Light stabilizer) Examples of the light stabilizer include hindered amine compounds and benzoate compounds.

[0047] (UV absorber) Examples of the ultraviolet absorbing agent include a benzophenone-based ultraviolet absorbing agent, a triazine-based ultraviolet absorbing agent, and a benzotriazole-based ultraviolet absorbing agent.

[0048] (Heavy metal deactivator) Heavy metal deactivators include salicylic acid derivatives, hydrazide derivatives, and oxalic acid amide derivatives.

[0049] (Fluorescent whitening agent) Examples of the fluorescent whitening agent include stilbene-based, coumarin-based, oxazole-based, and naphthalimide-based agents.

[0050] <Method of manufacturing hot melt adhesive> The manufacturing method of the hot melt adhesive is not particularly limited as long as the hot melt adhesive can be obtained. An example of the manufacturing method is as follows. The hot melt adhesive can be manufactured by heating a melting pot equipped with a stirrer to about 150°C, mixing and dispersing the thermoplastic elastomer into the heated and melted wax (C), oil, etc., adding a tackifier, and further mixing.

[0051] <Lump> The lump of the present invention is a lump containing the hot melt adhesive in the melting bag. The weight of the lump is preferably 10 g to 5000 g. If the weight is within the above range, it is easy to handle and has excellent workability in terms of the number of times it is filled, which is preferable. The thickness of the melting bag can be appropriately adjusted depending on the weight.

[0052] The hot melt adhesive to be contained in the melting bag may be an alkali-dispersible hot melt adhesive. PET bottles filled with soft drinks, seasonings, etc. and bottles filled with beer, sake, etc. are recycled or reused. Usually, in the process of recycling or reusing, there is a step of removing the labels attached to the PET bottles or bottles, and the labels are generally removed with a 1.5 to 4 mass % sodium hydroxide aqueous solution at about 85 to 95°C. Therefore, an alkali-dispersible hot melt adhesive is used for label applications. The present invention is suitable as a lump in which such an alkali-dispersible hot melt adhesive is packaged. The tackifier used in the alkali-dispersible hot-melt pressure-sensitive adhesive preferably contains a tackifier having an acid value of 100 to 300 mgKOH / g from the viewpoint of alkali dispersibility of the hot-melt pressure-sensitive adhesive. One example is a rosin-based tackifier. The acid value is the number of milligrams of potassium hydroxide (KOH) required to neutralize 1 g of sample, and is a value measured in accordance with JIS K5601-2-1 Acid Value (Titration Method).

[0053] (Method of manufacturing the aggregates) In the present invention, the method for producing an agglomerate containing a hot-melt pressure-sensitive adhesive is not particularly limited as long as it is capable of producing an agglomerate containing a hot-melt pressure-sensitive adhesive as intended by the present invention. For example, the following method can be mentioned as an example. The hot melt adhesive in the molten state is left at room temperature to solidify, producing a block of hot melt adhesive. The block of hot melt adhesive is then packaged in a mixed resin film (melt bag) to produce a mass. On the other hand, a block of hot melt adhesive may be produced by pouring heat-molten hot melt adhesive onto a mixed resin film and solidifying it, and at the same time, the block of hot melt adhesive may be packaged in the mixed resin film (melt bag).

[0054] ≪Container≫ The container in the present invention refers to a container to which a label is attached using a lump. The material of the container includes, but is not limited to, glass, plastic, paper, etc. In addition, the shape of the container may be round or non-round such as rectangular. The material of the container is preferably PET or glass, and more preferably PET.

[0055] In the case of PET bottles, in addition to the label attached to a part of the body of the PET bottle, the label is used as a roll label wound around the body of the bottle to cover it. OPP film is often used as such a roll label. The label of the present invention can be well adhered whether the back side is printed or not. In the present invention, the lump is coated on a part of the back side of the label. Coating methods include the open wheel method, the closed gun method, and the direct coat method. The open wheel method and the direct coat method are preferable as methods that do not leave glue on the PET bottle when peeled off.

[0056] The mass of the present invention can be used in the manufacture of sanitary materials, disposable medical drapes, paper, tapes and labels, furniture, textiles, footwear, wood processing or the building industry, for example, roofing membranes or other architectural type laminates. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the following examples. In the examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".

[0058] [Method for measuring the acid value of adhesive] The acid value was measured in accordance with JIS K5601-2-1 Acid Value (Titration Method). Specifically, 1 g of sample was precisely weighed and placed in a 250 ml flask, 50 ml of ethanol or a mixture of ethanol and ether was added, and the mixture was heated to dissolve, and titrated with 0.1N potassium hydroxide solution while occasionally shaking (indicator: phenolphthalein). The end point of the titration was the point at which the light pink color of the solution remained for 30 seconds. A blank test was then performed in the same manner to make corrections, and the acid value was calculated from the following formula. Acid value = [0.1N potassium hydroxide solution consumption (ml) x 5.611] / [sample amount (g)]

[0059] [Method of measuring the melting point of wax (C)] The melting point of the wax (C) was measured using a differential scanning calorimeter (Shimadzu Automatic Differential Calorimeter DSC-60A Plus). Approximately 5 mg of a sample was taken, cooled to 0°C, heated to 170°C at a heating rate of 10°C / min, and then cooled to 0°C at a cooling rate of -20°C / min. After being held at 0°C for 1 minute, it was heated again at a heating rate of 10°C / min, and the amount of heat released and absorbed when heated to 170°C was measured. The melting peak when the wax melted was taken as the melting point.

[0060] [Low density polyethylene resin (A)] Petrothene 205: Tosoh Corporation, density: 924kg / m 3 , MFR:3g / 10min Petrothene 230: Tosoh Corporation, density: 925kg / m 3 , MFR:8g / 10min Petrothene 208: Tosoh Corporation, density: 924kg / m3 , MFR:23g / 10min Petrothene 1384R: Tosoh Corporation, density: 928kg / m 3 , MFR: 7.6g / 10min Petrothene 173: Tosoh Corporation, density: 924kg / m 3 , MFR:0.3g / 10min Petrothene 209: Tosoh Corporation, density: 924kg / m 3 , MFR:45g / 10min

[0061] [Other low density polyethylene resins] Novatec LD LC720: Made by Japan Polyethylene Co., Ltd., density: 922kg / m 3 , MFR: 9.4g / 10min

[0062] [Ethylene-vinyl acetate copolymer resin (B)] Ultrasen 526: Tosoh Corporation, vinyl acetate content: 25% by mass Ultrasen 633: Tosoh Corporation, vinyl acetate content: 20% by weight Ultrasen 710: Tosoh Corporation, vinyl acetate content: 28% by mass Ultrasen 750: Tosoh Corporation, vinyl acetate content: 32% by weight Ultrasen 625: Tosoh Corporation, vinyl acetate content: 15% by mass

[0063] Wax Wax (C-1) PW655: Polyethylene wax manufactured by NuCera, melting point: 99℃ PW2000: Polyethylene wax manufactured by NuCera, melting point 126℃ Wax (C-2) PPMA6252: Ricosene PPMA6252, acid-modified polypropylene wax manufactured by Client Chemicals, melting point: 127°C Viscol 660P: Polypropylene wax manufactured by Sanyo Chemical Industries, melting point: 136℃ ·others HNP-9: Paraffin wax manufactured by Nippon Seiro Co., Ltd., melting point: 75℃ HNP-11: Paraffin wax manufactured by Nippon Seiro Co., Ltd., melting point: 68℃

[0064] [Antioxidants] IRG1010: Irganox 1010, manufactured by BASF, pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]

[0065] [Thermoplastic elastomer] G1650: Kraton G1650, Kraton Polymers, SEBS G1643: Kraton G1643, Kraton Polymers, SEBS G1652: Kraton G1652, Kraton Polymers, SEBS G1726: Kraton G1726, Kraton Polymers, SEBS D1118: Kraton D1118, Kraton Polymers, SBS

[0066] [Tackifier] RHR-301 (manufactured by China Wuzhou Sun Shine Forestry & Chemicals Co., LTD of Guangxi) hydrogenated rosin, acid value: 170mgKOH / g KE-604B: Pine Crystal KE-604B (Arakawa Chemical Co., Ltd.) Acrylic modified rosin, acid value: 230 mg KOH / g Alcon M-90 (Arakawa Chemical) Hydrogenated petroleum resin, acid value: none

[0067] [oil] N90: N-90 (Idemitsu Kosan), naphthenic process oil PW-90: Diana Process Oil PW-90 (Idemitsu Kosan), paraffin-based process oil PW-380: Diana Process Oil PW-380 (Idemitsu Kosan Co., Ltd.), paraffin-based process oil

[0068] <Production of mixed resin for melt bags> (Manufacturing example F-1) LDPE: 80 parts of Petrothene 205 and 20 parts of Ultrathene 710 were pre-blended and placed in the hopper of an IKG co-rotating twin screw extruder PMT32-40.5) and fed into the extruder using a screw feeder. The extrusion process was carried out under conditions of a screw rotation speed of 50 rpm and a feed rate of 5 kg / hr, resulting in a mixed resin of low-density polyethylene resin and ethylene-vinyl acetate copolymer resin.

[0069] (Manufacturing examples F-2~F-14) Using the compounding ratios shown in Table 1, mixed resins of Production Examples F-2 to F-14 were produced in the same manner as Production Example F-1.

[0070] [Table 1]

[0071] <Manufacturing of hot melt adhesives> (Manufacturing example: HM-1) The hot melt adhesive was produced by the following method. Wax: PPMA6252 (8 parts), oil: PW-90 (17 parts by weight), PW-380 (17 parts by weight), and antioxidant: IRG1010 (0.5 parts) were added to a stainless steel beaker equipped with a stirrer, and the contents were carefully heated to 130-150°C. After melting, the mixture was stirred to form a homogeneous molten solution, and then, while maintaining the temperature at 130-150°C and continuing to stir, 10 parts of thermoplastic elastomer: G1643 and 10 parts of G1652 were gradually added to the molten solution. After the addition was completed, the mixture was heated and stirred at a temperature of 130-150°C, and 38 parts of tackifier: RHR-301 were completely melted to form a homogeneous mixture, which was then cooled to produce a hot melt adhesive.

[0072] (Manufacturing example: HM-2~HM-10) Using the blending ratios shown in Table 2, Production Examples HM-2 to HM-10 were produced in the same manner as Production Example HM-1.

[0073] (Manufacturing example: HM'-1) In a stainless steel beaker equipped with a stirrer, 20 parts of oil: PW-90, 20 parts of PW-380, and 0.5 parts of antioxidant: IRG1010 were added, and the contents were carefully heated to 130 to 150°C. After melting, stirring was performed to obtain a uniform molten solution, and then 10 parts of thermoplastic elastomer: G1643 and 10 parts of G1652 were gradually added to the molten solution while maintaining the temperature at 130 to 150°C and continuing to stir. After the addition was completed, the mixture was heated and stirred at a temperature of 130 to 150°C to completely melt 40 parts of tackifier: RHR-301, and the mixture was cooled to produce a hot melt adhesive.

[0074] [Table 2]

[0075] [Example 1] The mixed resin (F-1) was formed on the release treatment layer of PET / release treatment layer (silicone treatment) using a T-die to obtain a mixed resin film with a thickness of 50 μm. The obtained mixed resin film was cut into 15 cm × 30 cm, folded to wrap 500 g of hot melt adhesive (HM-1), and the three open sides were heat sealed to obtain the lump (X) of Example 1.

[0076] [Examples 2 to 19 and Comparative Examples 1 to 5] The aggregates (X) of Examples 2 to 19 and Comparative Examples 1 to 5 were obtained in the same manner as in Example 1, except that the type of mixed resin, the thickness of the mixed resin film, and the type of hot melt adhesive were changed to those shown in Table 3.

[0077] (Bag breakability) Forty pieces of the lump (X) were placed in a cardboard box measuring 50 cm long x 38 cm wide x 30 cm high, and left in a 40°C oven for 24 hours, after which the state of the molten bag was visually inspected and evaluated. ◎, ◯, and △ were deemed acceptable, and × was deemed unacceptable. [Evaluation Criteria] ◎: No breakage of melted bag. Excellent. Good: The melted bag was broken, but the lumps were not bonded together. △: The melted bag was broken and the lumps were stuck together, but could be easily peeled off. No practical problem. ×: The melted bag was broken, and the lumps were stuck together and could not be peeled off. Not practical.

[0078] (Solubility) For HM-1 to HM-10 and HM'-1, white hot melt adhesives were prepared by blending 1% by mass of titanium oxide with respect to the total weight of the hot melt adhesive. The obtained mixed resin film was cut to 15 cm x 30 cm, folded to enclose 500 g of white hot melt adhesive, and the three open sides were heat sealed to obtain a lump (Y) containing the white hot melt adhesive. The lump (Y) was placed in a beaker and heated to 150°C, and then stirred for 1 minute at a stirring speed of 500 rpm using a stirring blade (IKA Japan, stirring blade R1381), and the molten material was dropped onto black paper and the color unevenness was visually evaluated. ◎, ◯, and △ were evaluated as pass, and × was evaluated as fail. [Evaluation Criteria] ◎: No color unevenness, excellent. ◯: Good, with some color unevenness in some areas. △: Although color unevenness was observed overall, there was no remaining melted part in the melting bag, and there was no problem in practical use. ×: Color unevenness was observed overall, and melted bags remained. Not suitable for practical use.

[0079] (Stringiness) The lump was placed in the melting tank of the hot melt gun, heated to 150°C, and intermittently coated 600 times directly sideways onto the adherend 30 cm away from the tip of the hot melt gun. The weight of the material that fell between the hot melt gun and the adherend was measured to evaluate stringiness. The test conditions were as follows, and the test was performed three times, with the average value being calculated. Discharge temperature: 140℃ Discharge amount: 0.2g / time Discharge time: 0.2 seconds Discharge interval: 0.2 seconds ◎, ◯, and △ were considered pass marks, and × was considered fail marks. [Evaluation Criteria] ◎: Less than 200mg, excellent. 〇: More than 200mg, less than 500mg, good. △: More than 500 mg, less than 1 g, no problem in practical use. ×: More than 1 g, or dissolved lumps clogged the nozzle, making application impossible. Not practical.

[0080] [Table 3]

[0081] [Table 4]

[0082] [Table 5]

[0083] From Tables 3 and 4, the aggregates containing a hot melt adhesive in a melting bag made of a mixed resin film have excellent solubility and bag-breaking properties, and good stringiness during labeling. On the other hand, in the comparative examples in Table 5, aggregates having excellent solubility and bag-breaking properties, and good stringiness during labeling, were not obtained.

Claims

1. A mass containing a hot melt adhesive in a melting bag, The density of the melting bag is 923-930 kg / m 3 and a mixed resin film containing a low-density polyethylene resin (A) and an ethylene-vinyl acetate copolymer resin (B), A mass in which the hot melt pressure sensitive adhesive contains a wax (C) and has a viscosity at 140°C of 500 to 2500 mPa·s.

2. 2. The aggregate according to claim 1, wherein the content of the ethylene-vinyl acetate copolymer resin (B) in 100% by mass of the mixed resin film is 10 to 50% by mass.

3. 2. The lump according to claim 1, wherein the ethylene-vinyl acetate copolymer resin (B) has a vinyl acetate content of 5 to 30% by mass.

4. Low density polyethylene resin (A) at 190°C and 2.16 kgf / cm 2 2. The aggregate according to claim 1, characterized in that the melt mass flow rate at is 1 to 25 g / 10 min.

5. 2. The lump according to claim 1, wherein the wax (C) has a melting point of 70 to 150°C.

6. 2. The lump according to claim 1, wherein the wax (C) contains at least one of a polyethylene-based wax (C-1) having a melting point of 90 to 150°C and a polypropylene-based wax (C-2) having a melting point of 90 to 150°C.

7. 2. The lump according to claim 1, wherein the thickness of the melt bag is 10 to 500 μm.

8. 7. The lump according to claim 6, characterized in that it contains a polypropylene-based wax (C-2) having a melting point of 90 to 150°C, and the wax (C-2) contains a polypropylene wax graft-polymerized with maleic anhydride.

9. 2. The lump according to claim 1, wherein the hot melt adhesive is an alkali dispersible hot melt adhesive.

10. A container having a label adhered thereto using the mass according to any one of claims 1 to 9.

11. 11. The container according to claim 10, wherein the material of the container is polyethylene terephthalate or glass.

Citation Information

Patent Citations

  • Film suitable for melted bag and melted bag

    JP2004002581A

  • Melting bag

    JP2014177284A

  • Thermoplastic resin film, melting bag and packaged hot melt adhesive

    JP2019065164A

  • Resin material for film molding, film-like molded body, meltable bag, and film manufacturing method

    JP2022083626A

  • Alkaline-dispersed hot-melt pressure-sensitive adhesive composition, method for producing same, method for attaching label, and container

    JP4278704B1